Reflective Shadows; Political Economy of the World Bank Lending to India - Prabhu, Nagesh (New Delhi, 2017)
This book maps the World Bank's economic clout, administrative influence, and manoeuvres through politics towards structural reforms of the Indian economy. It notes how the Bank was able to influence the country's economic and social policies through lending, as also the governments ability to resist this influence. It is a discourse on a world institution negotiating a country's policies for development and achieving the given goal of development
Keywords: Production